Biopreservation effects with Wickerhamomyces anomalus after 2 months moist airtight storage of sorghum - Nybogård, Louise (2016)
Today one third of all produced food is thrown away and one reason for this is microbial spoilage. Hunger and malnutrition in Africa could be reduced if the food loss is reduced. Wickerhamomyces anomalus is a possible biocontrol agent in food science that has shown antifungal and antibacterial effects on, for example, stored barley. The yeast produces ethyl acetate which suppresses mould growth. The mechanism for its antibacterial effect is still unknown. Sorghum bicolor is the second most important food crop for humans in Africa, which would benefit from a safe, stable storage method. In this experiment, 2 month-stored samples from three different storage methods were compared with each other and with 0 month samples from an earlier analysis, to see which method yielded the safest product, from a microbial hygiene perspective. Storage methods included traditionally open air dried, moist airtight with the yeast W. anomalus inoculated, and moist airtight as a control. Quantification and identification of Enterobacteriaceae, yeast, moulds and lactic acid bacteria (LAB) were performed by serial dilution on microbiological media, PCR, electrophoresis, DNA sequencing and database comparison. The result shows clear reductions in mould and Enterobacteriaceae amount in both control and inoculated samples compared to the dried sample. The inoculated sample had a significantly reduced amount of moulds in this study. It was also the only sample where the dominant yeast was W. anomalus. W. anomalus seems to be an efficient biocontrol agent in 2 month moist airtight stored sorghum. No sample was entirely free from mycotoxigenic moulds, and Aspergillus flavus and Penicillium citrinum were identified in both dried and inoculated samples. Enterobacteriaceae amounts decreased during 2 months storage, and previous studies show that there could be further reductions during extended storage. LAB had reduced in all samples and was not detected in the dried sample. Further studies should investigate if harvesting at a higher moisture content and crimping the sorghum could support a higher amount of LAB, which could be favorable for a more rapid reduction of undesirable microorganisms.